Enterprise 4.0 – the emerging digital transformed enterprise? - Moreira, Fernando (2018)
Information Systems are at the core of all businesses and cover almost all aspects of organizational life. The convergence of computer capabilities, such as the potential to process large volumes of data in a very short time, the growth in Internet usage and the increase in the ability to capture and leverage knowledge in digital format are, in this context, the main enablers of the so called digital transformation of organizations. While the technology enablers allow the production, sharing and management of information and knowledge within the organization between peers and other stakeholders, besides empowering the improvement and innovation of the organizational processes, they also require the updating of the supporting IS. Thus, using technologies in organizations within the context of Digital Transformation (DT) requires an exercise in understanding how to demonstrate their usefulness in relation to the creation, access and sharing of contents and IS improvements in a safe way. This paper provides a comprehensive view of a new context of labour faced within DT of organizations, which we term Enterprise 4.0 and which we propose to be implemented through the m_CSDIT framework, so as to improve the organizational well-being considering the collective intelligence and agility dimensions.